2007
DOI: 10.1021/jp0678960
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Reactive Metal Adsorption on Organic Thin Films

Abstract: We have studied the interaction of vapor-deposited Mg and Ca on −CH3, −COOH, −OH, −OCH3, and −CO2CH3 terminated self-assembled monolayers (SAMs) on polycrystalline Au{111} using time-of-flight secondary ion mass spectrometry and density functional theory calculations. Magnesium has a very low initial sticking probability on all of the SAMs studied. It inserts into the C−O bonds of oxygen-containing terminal groups and penetrates through methyl-terminated SAMs. In contrast, vapor-deposited calcium vigorously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 78 publications
0
43
0
Order By: Relevance
“…48 We have recently demonstrated that the conductivity of a Au/ODT/GaAs device is strongly dependent on its structure, 54 which in turn is related to the metal deposition conditions used. We vapor-deposited 150 Å of Au on an ODT SAM adsorbed on GaAs under three different deposition conditions, (a) direct deposition on a 300 K sample; (b) direct deposition on a 77 K sample; and (c) using a gentle deposition technique, Ar backfilling, on a 300 K sample.…”
Section: New Methods For the Metallization Of Organic Surfacesmentioning
confidence: 99%
“…48 We have recently demonstrated that the conductivity of a Au/ODT/GaAs device is strongly dependent on its structure, 54 which in turn is related to the metal deposition conditions used. We vapor-deposited 150 Å of Au on an ODT SAM adsorbed on GaAs under three different deposition conditions, (a) direct deposition on a 300 K sample; (b) direct deposition on a 77 K sample; and (c) using a gentle deposition technique, Ar backfilling, on a 300 K sample.…”
Section: New Methods For the Metallization Of Organic Surfacesmentioning
confidence: 99%
“…For the alkaline earth metals this effect can be useful for generating low work function cathode metal electrodes in organic light emission diodes (OLEDs) and organic electro luminescence display (OELDs). Alkaline earth metals, however, are not only active in injecting electrons into conjugated molecules but also are chemically reactive and can form reaction products with many organic groups [56,57]. In general, the alkali metals are not used for commercial applications but are useful to study for their simple behavior as one electron injection atoms.…”
Section: Timentioning
confidence: 99%
“…In the case of Mg and Ca depositions on n-alkanethiolate SAMs it was observed that while Mg does not react it does undergo continuous penetration thorough the SAM. In contrast, Ca does react to some extent resulting in calcium carbide species formation [56,57]. In the case of K on an n-alkanethiolate SAM the results are more complicated.…”
Section: Reactivity With Inert Samsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many outcomes have been observed, from metal atom penetration through the organic layer to destruction of the monolayer via carbide formation to formation of strongly bound complexes and stable contact formation [17]. Although the interaction of vapor-deposited metals with SAMs is governed by a single reaction pathway, it is not easy to predict the outcome of a particular interaction [17]. Technologies besides PVD to deposit metals and other materials in Si-based microelectronics include CVD [18], atomic layer deposition (ALD) [19] and electrodeposition [20].…”
Section: Electroless Depositionmentioning
confidence: 99%